Fast X [videorecording (DVD)] - Mazeau, Dan; Lin, Justin; Dean, Zach; Diesel, Vin; Rodriguez, Michelle; Tyrese; Ludacris (Rapper); Cena, John; Emmanuel, Nathalie, 1989-; Brewster, Jordana, 1980-; Kang, Sung, 1972-; Eastwood, Scott, 1986-; et al. (Universal, 2023)
Over many missions and against impossible odds, Dom Toretto and his family have outsmarted, out-nerved and outdriven every foe in their path. Now, they confront the most lethal opponent they've ever faced: A terrifying threat emerging from the shadows of the past who's fueled by blood revenge, and who is determined to shatter this family and destroy everything and everyone that Dom loves, forever.